Immediate versus delayed palliative thoracic radiotherapy in patients with unresectable locally advanced non-small cell lung cancer and minimal thoracic symptoms: randomised controlled trial - Falk, Stephen J (BMJ, 2002)
OBJECTIVE: To determine whether patients with locally advanced non-small cell lung cancer unsuitable for resection or radical radiotherapy, and with minimal thoracic symptoms, should be given palliative thoracic radiotherapy immediately or as needed to treat symptoms. DESIGN: Multicentre randomised controlled trial. SETTING: 23 centres in the United Kingdom, Ireland, and South Africa. PARTICIPANTS: 230 patients with previously untreated, non-small cell lung cancer that is locally too advanced for resection or radical radiotherapy with curative intent, with minimal thoracic symptoms, and with no indication for immediate thoracic radiotherapy. INTERVENTIONS: All patients were given supportive treatment and were randomised to receive palliative thoracic radiotherapy either immediately or delayed until needed to treat symptoms. The recommended regimens were 17 Gy in two fractions one week apart or 10 Gy as a single dose. MAIN OUTCOME MEASURES: Primary—patients alive and without moderate or severe cough, chest pain, haemoptysis, or dyspnoea six months from randomisation, as recorded by clinicians. Secondary—quality of life, adverse events, survival. RESULTS: From December 1992 to May 1999, 230 patients were randomised. 104/115 of the patients in the immediate treatment group received thoracic radiotherapy (90 received one of the recommended regimens). In the delayed treatment group, 48/115 (42%) patients received thoracic radiotherapy (29 received one of the recommended regimens); 64 (56%) died without receiving thoracic radiotherapy; the remaining three (3%) were alive at the end of the study without having received the treatment. For patients who received thoracic radiotherapy, the median time to start was 15 days in the immediate treatment group and 125 days in the delayed treatment group. The primary outcome measure was achieved in 28% of the immediate treatment group and 26% of patients from the delayed treatment group (27/97 and 27/103, respectively; absolute difference 1.6%, 95% confidence interval –10.7% to 13.9%). No evidence of a difference was observed between the two treatment groups in terms of activity level, anxiety, depression, and psychological distress, as recorded by the patients. Adverse events were more common in the immediate treatment group. Neither group had a survival advantage (hazard ratio 0.95, 0.73 to 1.24; P=0.71). Median survival was 8.3 months and 7.9 months, and the survival rates were 31% and 29% at 12 months, for the immediate and delayed treatment groups, respectively. CONCLUSION: In minimally symptomatic patients with locally advanced non-small cell lung cancer, no persuasive evidence was found to indicate that giving immediate palliative thoracic radiotherapy improves symptom control, quality of life, or survival when compared with delaying until symptoms require treatment.